Towards a Better Characterisation of Leukemic Cells in Chronic Lymphocytic Leukaemia: Cell-Size Heterogeneity Reflects Their Activation Status and Migratory Abilities - Manukyan, Gayane; Mikulkova, Zuzana; Turcsanyi, Peter; Savara, Jakub; Trajerová, Markéta; Kubova, Zuzana; Papajik, Tomas; Kriegova, Eva (Cancers, 2021)
Chronic lymphocytic leukaemia (CLL) is a genetically, morphologically and phenotypically heterogeneous chronic disease with clinical variability between patients. Whether the significant heterogeneity of cell size within the CLL population contributes to the heterogeneous features of this disease has not been investigated. The present study aimed to characterise the phenotypic and functional properties of two subpopulations of typical CLL cells that differ in cell size: small (s-CLL) and large (l-CLL) CLL cells delineated by forward scatter cytometry. The s-CLL cells were characterised by the CD5lowCXCR4hi phenotype, while the l-CLL cells were characterised by the CD5hiCXCR4dim phenotype and indicated a higher expression of CXCR3, CD20, CD38 and HLA-DR. The l-CLL cells displayed higher migration activity towards CXCL12, a tendency towards a higher proliferation rate and an increased capacity to produce IgM in the presence of CpG compared with s-CLL cells. When stimulated with CpG and CXCL12, l-CLL cells were characterised by a higher polarisation phenotype and motility than s-CLL cells. Our study revealed that the differences in CLL cell size reflected their activation status, polarisation and migratory abilities. Our data provide evidence of the importance of cell-size heterogeneity within a CLL pool and the dynamics of cell-size changes for disease pathogenesis, thus deserving further investigation.
Keywords: pool of leukemic cells; chronic lymphocytic leukaemia; migration; cell-size heterogeneity; polarisation